2019
DOI: 10.3390/su11247049
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Soil Characteristics of Sandy Loam Soil and Grain Quality of Spring Maize by Using Phosphorus Solublizing Bacteria

Abstract: Unavailability of balanced nutrients in nutrient-deficient soils is the key reason in reduced yields of spring maize. After application to soil, most of the phosphorus (80–90%) is lost in the environment because of runoff losses and chemically bonding. So, this makes the phosphorus unavailable for plant use. However, soil microorganisms may provide a biological rescue system which is able to solubilize the soil-bound phosphorus (p). Keeping this in view, the present study is designed to meet the following obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Adnan et al [110] demonstrated significant improvement in maize growth with PSB inoculation, especially when combined with different types of inorganic and organic P fertilizers. Similarly, Javeed et al [131] observed enhanced maize growth parameters with PSB inoculation in conjunction with NPK fertilizer. Suleman et al [132] reported increased P uptake and use efficiency in wheat plants inoculated with Pseudomonas sp.…”
Section: Advances In Agriculturementioning
confidence: 86%
“…Adnan et al [110] demonstrated significant improvement in maize growth with PSB inoculation, especially when combined with different types of inorganic and organic P fertilizers. Similarly, Javeed et al [131] observed enhanced maize growth parameters with PSB inoculation in conjunction with NPK fertilizer. Suleman et al [132] reported increased P uptake and use efficiency in wheat plants inoculated with Pseudomonas sp.…”
Section: Advances In Agriculturementioning
confidence: 86%
“…Similarly, due to the improved water retention following inoculation of maize plants with Enterobacter sakazakii observed by Javeed et al (2019), the effects of inoculating soils with microbes from genera other than Bacillus may also be studied in the absence plants to determine the mechanisms by which each genus alters soil moisture dynamics. Finally, the optimal concentration and application rates of B. subtilis should be investigated as these will determine the financial feasibility of using inoculation in a production agriculture setting.…”
Section: Discussionmentioning
confidence: 99%
“…Seed formation is supported by the availability of nutrients [41]. Adequate phosphorus availability can support seed formation and improve seed quality [42]. The improved seed quality is indicated by the higher weight of one hundred seeds.…”
Section: Corn Yieldmentioning
confidence: 99%